THE ROLE OF BLOCKCHAIN TECHNOLOGY IN THE UNIVERSAL METAVERSE FROM THE PERSPECTIVE OF COMPETITIVE RELATIONS IN BUSINESS. CHALLENGES AND UNCERTAINTIES - PAUN, Roxana Daniela (Annals of Spiru Haret University. Economic Series, 2022)
Blockchain technology is becoming one of the most prominent trends in finance and digital innovation since the creation of the Internet. Blockchain technology makes data private, permanent and verifiable. Data and transaction logging is public, but encryption protects them from prying eyes and tampering. The architecture of the blockchain database and the associated protocols provide a solid foundation for creating new classes of applications. This is just the theory. In practice, however, blockchain technology has proven to be somewhat less miraculous. It is powerful and effective in a wide range of areas, but in addition to the well-publicized benefits of blockchain, experts have discovered a set of disadvantages of blockchain technology. That's why the Bitcoin blockchain is often referred to as the "open register" of Bitcoin. Experts around the world, with the exception of a few skeptics, see blockchain as a high-impact technology that has the potential to revolutionize the world of finance, gaming, entertainment and more. Starting from the analysis carried out by specialists in the field on their website, and from information on this technology, the present study brings some arguments to draw the attention of the more or less informed reader to the risks and dangers to which they are exposed and to whom this technology is applied in sensitive areas regarding the life, health, freedom and privacy of the citizens of this planet. Even if the role of this technology in some fields is undeniable, it must still be treated with great care from the perspective of respecting the fundamental rights and freedoms of human beings, the universal values that mankind has gained in centuries of human effort and sacrifice for current and future generations to evolve without repeating the mistakes of history. History makes fun of those who do not know it, repeating itself, said Nicola Iorga.